An Initial Covalent Organic Polymer with Closed‐F Edges Directly for Proton‐Exchange‐Membrane Fuel Cells. Issue 36 (9th August 2022) - Li, Xueli; Liu, Qingbin; Yang, Bolong; Liao, Zhijian; Yan, Wensheng; Xiang, Zhonghua
Abstract: Covalent organic polymers (COPs) are a class of rising electrocatalysts for the oxygen reduction reaction (ORR) due to the atomically metrical control of the organic molecular components along with highly architectural robustness and thermodynamic stability even in acid or alkaline media. However, the direct application of pristine COPs as acidic ORR electrocatalysts, especially in device manner, e.g., in proton‐exchange‐membrane fuel cells (PEMFCs), remains a big challenge. Currently, the decoration toward electronic structures of active sites is considered a vital pathway to enhancing the acidic ORR activity of carbon‐based electrocatalysts. Here, an initial F‐decorated fully closed π‐conjugated quasi‐phthalocyanine COP (denoted as COPBTC ‐F) is reported. The introduction of the closed‐F edges stepwise drags more electrons from FeN4 sites in COPBTC ‐F into the catalyst margin, which weakens the occupied numbers of bonding orbitals between COPBTC ‐F and OH* intermediates at the rate‐determining step, exhibiting over five times intrinsic performance beyond the counterpart without F functionalities (termed as COPBTC ). Significantly, the maximum power density utilizing COPBTC ‐F as a cathode catalyst in PEMFCs is remarkably increased by an order of magnitude compared with COPBTC, which is a stride forward among catalysts based on a pyrolysis‐free conjugated‐polymer network in device manner to date. Abstract : An initial F‐decorated quasi‐phthalocyanine covalent organic polymer is prepared, which delivers exceptional catalytic activity in the acidic oxygen reduction reaction and has capability to be directly applied into proton‐exchange‐membrane fuel cells devices, which is a stride forward among catalysts based on a pyrolysis‐free conjugated‐polymer network in device manner to date.